Software Tools for Predicting the Success of Advertising Campaigns - Dyachenko, L.; Teodorovych, L. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2025)
The article examines the distinctive features of contemporary marketing and advertising tools. The study identifies predictive analytics, implemented through specialised software, as a powerful instrument for achieving more accurate forecasting and informed decision-making in marketing. Predictive analytics in this field employs machine learning, statistical modelling, and big data analysis to anticipate consumer behaviour, assess the effectiveness of advertising campaigns, and identify market trends. Modern advertising-monitoring software enables the tracking of competitors’ media activity, the analysis of reach and engagement, and the automated evaluation of creative performance. Consumer-research tools integrate audience segmentation, sentiment analysis, and automated insight generation, thereby assisting companies in more precisely determining the needs of target groups and optimising communication strategies. The paper presents an overview of the most widespread software solutions, analysing their functional capabilities, modelling approaches, and the ease with which they can be integrated into marketing processes.